New nonlinear estimators of the gravity equation - Ayman Mnasri (16932486) (2021)
The gravity model of international trade is often applied by economists to explain bilateral trade between countries. Nevertheless, some estimation practices have been subject to criticism, namely how zero trade values and the heteroskedasticity are handled. This paper proposes new nonlinear estimation techniques to address these issues. In particular, we propose standard and generalized versions of the nonlinear Heckman two-step approach that do not require the log-linearization of the gravity equation and corrects for non-random selection bias, and a generalized nonlinear least squares estimator that can be viewed as an iterative version of the normal family Quasi-Generalized Pseudo-Maximum-Likelihood estimator. Monte Carlo simulations show that our proposed estimators outperform existent linear and nonlinear estimators and are very efficient in correcting the selection bias and reducing the standard deviation of the estimates. Empirical results show that previous studies have overestimated the contribution of variables such as importer’s income, distance, remoteness, trade agreements, and openness. Other Information Published in: Economic Modelling License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.econmod.2020.12.011